Risk of comorbid cardiovascular disease in Korean long‐term cancer survivors. (21st August 2019) - Shin, Jinyoung; Ko, Hyeonyoung; Choi, Yoon‐Ho; Choi, Inyoung; Song, Yun‐Mi
Abstract: Background: Cardiovascular disease (CVD) is a common cause of death in cancer survivors. We evaluated the risk of comorbid CVD in long‐term cancer survivors according to specific cancer site. Methods: Study subjects included 47, 171 Koreans aged over 40 years who visited a health promotion centre between 2010 and 2012. Information on CVD and cancer was obtained from self‐report. Comorbid CVD was defined as stroke, myocardial infarction or angina pectoris. The risk of comorbid CVD in survivors was compared with that in non‐cancer subjects using multiple logistic regression analysis. Results: Among cancer survivors ( n  = 3, 753), 330 events of CVD were reported. Age‐ and sex‐adjusted analysis showed that odds ratio (OR) for comorbid CVD in survivors was 1.52 (95% confidence interval: 1.34–1.72) compared to non‐cancer subjects ( n  = 43, 418). After adjusting for health‐related behaviour and medical history, only lung cancer survivors had 2.44 (1.01–5.89)‐fold higher OR for CVD. In stratified analysis, significantly higher OR for CVD was evident in lung cancer survivors with hypertension who did not perform regular physical exercise. Conclusions: Adult cancer survivors may have an increased risk of comorbid CVD that might be mediated in part by known cardiovascular risk factors depending on the specific cancer site.